Fisiologia de plantas de meloeiro cultivadas sob diferentes níveis de irrigação - Silveira, Enio Marques de Castro (2013)
The melon is the most exports of fresh fruit produced in Brazil, especially being produced in the states of Rio Grande do Norte and Ceará. All this curcubitaceae commercial orchard in the two regions is performed under irrigated conditions. Thus, measures of efficient use of water become essential for this crop. The improvement in efficiency of water use will depend primarily on a management plan that deliver only the amount of water necessary for their full development. The study aimed to evaluate plant growth, water status, gas exchange and yield of yellow melon grown under different irrigation levels. Therefore, two experiments were conducted in the experimental field of Curu, Paraipaba, CE, using hybrid Gold Mine, with spacing of 2.0 m x 0.4 m, under drip irrigation. The first experiment consisted of weekly evaluation of plant growth in response to applying three different irrigation water levels: 100% 80% and 120% (T1, T2 and T3 respectively) of calculated levels. In the second experiment, in addition to the treatments mentioned above, was inserted another factor: the irrigation schedule of 24 to 48 hours, with four replicates. In this it, was evaluated gas exchange, water potential, the carbohydrate in different parts of the plant, yield and fruit quality. In all treatments the plants showed the lowest water potential daily between 12:00 to 2:00pm. Although stomatal conductance decreases during the day curse, it remained in amounts sufficient for photosynthetic rate nearly constant, with a slight reduction after noon and marked decrease only after 4:00pm. In turn, with the exception of transpiration, which was higher in plants irrigated every 48 hours, the irrigation water levels and the irrigation schedule did not affect gas exchange of plants. Likewise, the production, the size and quality of melon fruits were practically not influenced by treatments. Thus, under the experimental conditions used, the increase or decrease of 20% of irrigation water level calculated and recommended to the melon in the region, did not affect plant development, nor the production. Only the amount of total soluble solids was positively influenced by the addition of 20% of the water levels calculated, when applied daily